Krimy's Enterprise - Abd Hamid, Hamidah; Adin, Norafidah; Hamid, Sharifah Marlina; Puasah, Siti Masura; Ab Karim, Siti Zuraikah (2012)
Krimy's Enterprise is a partnership business and doing a retail business. Its main activity is producing a fried ice cream and sent it to every market. Our brand for the product is "aiskrimoo". We choose krimy's Enterprise as our company's name because it easy for people to remember it and it relate with our product's brand. Selecting the location Krimy's enterprise is based on strategic place for our operation in factory. Purpose business of krimy's Enterprise is to fulfill need and want society in Sabah to try a new product of "aiskrimoo" which is fried ice cream that a new for them. Next is providing a high quality product like a consumer taste. Besides that, the purpose is to enter in Sabah market. It because this product still not available in Sabah. So, our company wants to take this opportunity to start the business and enter the market. As an entrepreneur, we will always find or create something new and innovate the product to become different from our competitor. Krimy's Enterprise has a good and creative idea to upgrade the product from time to time. So, the prospect will not disappoint with the Aiskrimoo's product. Like other business, our company also has a competitor but our competitor is at peninsular Malaysia. It because fried ice cream only exist in peninsular Malaysia. But it does not mean that we no need to compete with them just because they are in peninsular Malaysia. We will try the best to compete with them and take a competitive advantage. The financial of Krimy's Enterprise is from a loan and contributes by each partner. All partnership agrees to contribute 24% from our capital to start a business and 76% from a loan. The analysis that have made from the research, we find that Aiskrimoo's product will became a first choice in the future and remain grow because our company can give a good product that have a high quality product.